United States Biofuel Policies: Overview and Discussion - Zhengfei Guan; Juhyun Oh (EDIS)
Governments at different levels in the United States have introduced various programs to promote alternative and renewable energies, reduce greenhouse gas emissions, and improve energy security. Some of these policy initiatives include mandates and tax credits to encourage the production of biofuels. As governmental efforts to promote renewable fuels as alternative sources of energy have evolved from subsidization to mandate, the production of biofuels has dramatically increased. The expansion of the mandate may contribute to reducing greenhouse gas emissions, but biofuels may be technically, economically, and environmentally inefficient. This 4-page fact sheet reviews and discusses current US biofuel policies and explores potential outcomes. Written by Zhengfei Guan and Juhyun Oh, and published by the Food and Resource Economics Department, November 2015.